Corporate decision making in the presence of political uncertainty: The case of corporate cash holdings. Issue 2 (26th May 2019) - Hankins, William B.; Stone, Anna‐Leigh; Cheng, Chak Hung Jack; Chiu, Ching‐Wai (Jeremy)
Abstract: Using a quarterly panel of U.S. corporations over the period 1985–2014, we show that corporate managers respond to political uncertainty and economic policy uncertainty shocks in different ways. We proxy for political uncertainty using the Partisan Conflict Index and employ a prevalent empirical macroeconomic methodology to construct structural shocks that are orthogonal to shocks captured by the Economic Policy Uncertainty Index. Following a political uncertainty shock, corporations increase cash but do not adjust investment. Alternatively, following an economic policy uncertainty shock, firms appear to draw on cash and reduce capital spending to increase research and development spending.